Sulfated zwitterionic poly(sulfobetaine methacrylate) hydrogels promote complete skin regeneration - Wu, Jiang; Xiao, Zecong; Chen, Anqi; He, Huacheng; He, Chaochao; Shuai, Xintao; Li, Xiaokun; Chen, Shengfu; Zhang, Yanxian; Ren, Baiping; Zheng, Jie; Xiao, Jian (Acta biomaterialia, 2018)
[Display omitted] Skin wound healing is a still long-history challenging problem and impeded by the foreign-body reaction including severe inflammation response, poor neovascularization, incomplete re-epithelialization and defective ECM remodeling. Development of biocompatible polymers, in combination with specific drugs or growth factors, has been considered as a promising strategy to treat skin wounds. Significant research efforts have been made to develop poly(ethylene glycol) PEG-based polymers for wound healing, however less efforts has been paid to zwitterionic materials, some of which have demonstrated their super low-fouling property in vitro and anti-inflammatory property in vivo. Here, we synthesized ultra-low-fouling zwitterionic sulfated poly(sulfobetaine methacrylate) (polySBMA) hydrogels and applied them to full-thickness cutaneous wounds in mice. The healing effects of SBMA hydrogels on the wound closure, re-epithelialization ratio, ECM remodeling, angiogenesis, and macrophage responses during wound healing processes were histologically evaluated by in vivo experiments. Collective results indicate that SBMA hydrogels promote full-thickness excisional acute wound regeneration in mice by enhancing angiogenesis, decreasing inflammation response, and modulating macrophage polarization. Consistently, the incorporation of SBMA into PEG hydrogels also improved the overall wound healing efficiency as compared to pure PEG hydrogels. This work demonstrates zwitterionic SBMA hydrogels as promising wound dressings for treating full-thickness excisional skin wounds. Development of highly effective wound regeneration system is practically important for biomedical applications. Here, we synthesized ultra-low-fouling zwitterionic sulfated poly(sulfobetaine methacrylate) (polySBMA) hydrogels and applied it to full-thickness cutaneous wounds in mice, in comparison with PEG hydrogels as a control. We are the first to examine and reveal the difference between zwitterionic SBMA hydrogels and PEG hydrogels using a full-thickness excisional mice model. Overall, a series of in vivo systematic tests demonstrated that zwitterionic SBMA hydrogels exhibited superior wound healing property in almost all aspects as compared to PEG hydrogels.